ANALYSIS OF BASE SEDIMENT & WATER EFFECT ON INTERNAL CORROSION RATE OF PIPELINE API 5L Gr B: ANALYSIS OF BASE SEDIMENT & WATER EFFECT ON INTERNAL CORROSION RATE OF PIPELINE API 5L Gr B - Muhammad iqbal Pangindoman; Ahmad Zikri; Selastia Yuliati (KINETIKA, 2022)
Base Sediment & Water (BS&W) is indicated high has to be as a corrosion factor in the pipeline. Corrosion is the damage or degradation of metals due to oxidation-reduction reactions between a metal and various substances in its environment which produce unnecessary compounds. Corrosion can be influenced by several factors, such as NaCl content, BS&W composition, dissolved gas content, pH, flow rate and temperature. The composition of BS&W can have an impact on the corrosion rate of the API 5L Gr B steel pipe.   Keywords : Pipeline, BS&W, Corrosion Rate